HUBUNGAN POLA PENGGUNAAN MEDIA SOSIAL DENGAN PERILAKU MAKAN DAN AKTIVITAS FISIK PADA REMAJA DI DKI JAKARTA - Salsabila Nur Idzhni Amalia (2023)
Social media is one of the most utilized technological developments. The use of social media in adolescents can indirectly affect nutritional status because it can affect a person's physical activity and eating behavior. This happens because of the times that cause lifestyle changes, especially in adolescents through social media. This study aims to determine the relationship between patterns of social media use with eating behavior and physical activity in adolescents at DKI Jakarta. This study used a cross sectional design with a sample of 187 respondents taken with stratified random sampling technique. Data were collected through questionnaires, Food Frequency Questionnaire (FFQ), and International Physical Activity Questionnaire (IPAQ). Relationship analysis conducted using the chi-square test shows that there is a relationship between frequency (p = 0.022) and duration (p = 0.003) with eating behavior, there is no relationship between exposure to culinary content (p = 0.228), there is a relationship between frequency (p = 0.021) and duration (p = 0.005) with physical activity, and there is no relationship between exposure to physical activity content (p = 0.157) with physical activity in adolescents in DKI Jakarta.